Anaesthesiological managemnet at paediatric cardiac surgical centres in Germany: Current status of personnel and structural organisation Anästhesiologische Versorgung an deutschen Zentren für Kinderherzchirurgie: Aktueller Stand der personellen und strukturellen Organisation - Bähner, T.; Heinze, I.; Mueller, M.; Schindler, E.; Schirmer, U.; Hoeft, A.; Baumgarten, G.; Ellerkmann, R. K.; Dewald, Oliver (Anästhesiologie & Intensivmedizin, 2016)
Background: Owing to its complexity paediatric cardiac anaesthesia requires a high level of expert knowledge. There are currently no recommendations for standards in paediatric cardiac anaesthesia in Germany. The aim of the present study was to assess the current structural and personnel anaesthetic standards in paediatric cardiac surgical centres in Germany. Method: The participating centres were interviewed using an online questionnaire to assess current practice in paediatric cardiac anaesthesia. The questionnaire contained 55 items subdivided in 16 categories on 30 pages. Results: An active programme for congenital heart surgery was identified in 27 hospitals in Germany. The questionnaire response rate was 96.3%. A specialised group of anaesthesiologists concerned with paediatric cardiac anaesthesia was reported to exist by 92.3% of participating centres, with a mean size of 4.8 anaesthesiologists per group in each centre. However, the annual case load of each anaesthesiologist varies considerably. Currently, only 26.9% of the centres ensure an intraoperative management by two anaesthesiologists per patient. An additional supervisor is present in 53.8% of the centres. Sedation and general anaesthesia for diagnostic and therapeutic interventions outside the operating theatre in patients with congenital heart disease is also performed by non-anaesthesiologists in 76.9% of the centres. Special equipment, e.g. mechanical autotransfusion, ultrasound for vascular access, transoesophageal echocardiography and near-infrared spectroscopy is mostly available but not often routinely used. Conclusion: This study presents the current structural and personnel standards for paediatric cardiac anaesthesia at the centres for congenital heart surgery in Germany.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Congenital Heart Disease; Congenital Heart Surgery; Paediatric Cardiac Anaesthesia